Urban agroecology enhances agrobiodiversity and resilient, biocultural food systems. The case of the semi-dryland and medium-sized Querétaro City, Mexico - Villavicencio-Valdez, Gabriela Valeria; Jacobi, J.; Schneider, M.; Altieri, M. A.; Suzán-Azpiri, H. (Frontiers in Sustainable Food Systems, 2023)
Small-scale agroecological practices in the urban areas of Querétaro, México, as in other mid-sized cities, could maintain agrobiodiversity pools and sufficient productivity for a food sovereignty baseline. The application of agroecological principles fosters agrobiodiversity and socio-ecological resilience in urban food production. Emerging urban gardens result from an immediate necessity for food that does not appear in local statistics, nor is there any account of them in any cadastral source or land register of Querétaro City. Based on studies of 28 urban gardens, we survey and analyze farming practices using socio-ecological resilience methodologies and the Diagnostic Survey of Agroecological Practices. We find that the agroecological management of urban gardens results in significantly more species richness than in conventionally managed plots, likely due to the multifunctional purposes associated with biocultural memory. The number of social actors participating in agroecological management is increasing. It represents an urban strategy of resilience that contributes to enhancing the microclimate and nutrient cycling, as well as to improving water management and biodiversity. Results also indicate that gardens of approximately 200 m2 harbor the highest levels of agrobiodiversity. This area size for home vegetable production appears optimal for user-friendly management practices in urban settings and could represent the minimum benchmark for a family and a goal for urban planning and policy recommendations. Urban gardens contribute to the adaptive capacities of city dwellers to enhance their food security and sovereignty. Therefore, given that 70% of the national population face some level of food insecurity, we argue that, along with the protection of land-use rights, the promotion of a diverse urban landscape could improve long-term socio-ecological and food supply resilience. Additionally, urban gardens promote neighborhood social inclusion and affordable access to food. The empirical results and insights from this study in Querétaro can inform land-use policies for urban agriculture more broadly, especially in Latin American metropolitan areas.